La casa di Ivan Il’ič - Andrea Mecacci (eSamizdat)
The essay analyses the social and aesthetic meanings of the intérieur in reference to Tolstoy’s short novel The Death of Ivan Il’ič. Relying on Walter Benjamin’s considerations on the bourgeois intérieur, the essay interprets the indissoluble link between the world of the inanimate (object) and the fetishization processes of the social body. This analysis briefly integrates two films, The Irony of Fate and Loveless, which revisit the legacy of Tolstoy’s story, showing the dialectic between home and house as its decisive paradigm.